Komunikatywno-pragmatyczny aspekt czerwieni (na przykładzie książki „У войны не женское лицо” Swietłany Aleksijewicz) - Słupianek-Tajnert, Daria (Studia Rossica Posnaniensia, 2019)
The article presents the role of the colour red in defining two communicative and pragmatic centres (the war and the woman) in Svetlana Alexievich’s reportage War Does Not Have a Woman’s Face. The colour red plays a significant role in visualizing war events and depicting different aspects of female sensitivity.